Caring for children with learning disabilities who present problem behaviours: a maternal perspective. - Johnson RF; O'Reilly M; Vostanis P (Journal of Child Health Care, 2006)
The theoretical cognitive model of stress and coping provides a structure to obtain and analyse maternal perceptions of caring for children with learning disabilities who present severe problem behaviours. The Family Fund database identified 18 families who met the sample criteria of children aged five years to 15 years with severe to moderate learning disability presenting severe problem behaviour. Physical aggression was reported to be the primary behavioural problem for 13 of the children. Interviews undertaken with the main carer of the child at their home were taped and transcribed. The data were analysed using grounded theory techniques which identified 'secondary stressors' for the parent. These were social isolation, conflict, limitation of lifestyle and self-blame. It is proposed that the amalgamated impact of these can weaken parents' coping resources and, therefore, may prove to be as significant to the negative association with maternal wellbeing as the problem behaviour.